Genome-Wide Study of YABBY Genes in Upland Cotton and Their Expression Patterns under Different Stresses - Yang, Zhaoen; Gong, Qian; Wang, Lingling; Jin, Yuying; Xi, Jianping; Li, Zhi; Qin, Wenqiang; Yang, Zuoren; Lu, Lili; Chen, Quanjia; Li, Fuguang (Frontiers in Genetics, 2018)
Members of the YABBY gene family, a small plant-specific family of genes, have been proposed to function in specifying abaxial cell fate. Although to date little has been learned about cotton YABBY genes, completion of the cotton genome enables a comprehensive genome-wide analysis of YABBY genes in cotton. Here, a total of 12, 12, and 23 YABBY genes were identified in Gossypium arboreum (2n = 26, A2), G. raimondii (2n = 26, D5), and G. hirsutum (2n = 4x = 52, [AD]t), respectively. Sequence analysis showed that the N-terminal zinc-finger and C-terminal YABBY domains in YABBY proteins are highly conserved among cotton, Arabidopsis, and rice. Eighty-five genes from eight sequenced species naturally clustered into five groups, and the YAB2-like group could be divided into three sub-groups, indicating that YABBYs are highly conserved among the examined species. Orthologs from the At and Dt sub-genomes (where “t” indicates tetraploid) showed good collinearity, indicating that YABBY loci are highly conserved between these two sub-genomes. Whole-genome duplication was the primary cause of upland cotton YABBY gene expansion, segmental duplication played important roles in YABBY gene expansion within the At and Dt sub-genomes, and the YAB5-like group was mainly generated by segmental duplication. The long-terminal repeat retroelements Copia and Gypsy were identified as major transposable elements accompanying the appearance of duplicated YABBY genes, suggesting that transposable element expansion might be involved in gene duplication. Selection pressure analyses using PAML revealed that relaxed purifying selection might be the main impetus during evolution of YABBY genes in the examined species. Furthermore, exon/intron pattern and motif analyses indicated that genes within the same group were significantly conserved between Arabidopsis and cotton. In addition, the expression patterns in different tissues suggest that YABBY proteins may play roles in ovule development because YABBYs are highly expressed in ovules. The expression pattern of YABBY genes showed that approximately half of the YABBYs were down-regulated under different stress treatments. Collectively, our results represent a comprehensive genome-wide study of the YABBY gene family, which should be helpful in further detailed studies on the gene function and evolution of YABBY genes in cotton.